INTELLECTUAL CAPITAL DAN KINERJA KEUANGAN PADA SEKTOR INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA - Yulindisti, Elga; Helmi, Syarif M. (APSSAI, 2024)
The study examines the effect of intellectual capital on financial performance. The independent variable is intellectual capital measured with value-added intellectual capital (VAIC) and its components: value-added human capital (VAHU), value-added capital employed (VACA), and structural capital value added (STVA). In contrast, the dependent variable is financial performance as measured by the return on assets (ROA) and return on equity (ROE). The moderating in this study is firm size as measured by the total assets. This sample consists of 190 samples of the consumer goods industry sector on the Indonesia Stock Exchange (IDX) from 2017-2021. The finding is that VAIC has a significant effect on financial performance, and VAHU and VACA have a significant effect on financial performance. In comparison, STVA has no significant effect on financial performance. Firm size moderates the relationship between VAIC, VAHU, and VACA on financial performance. While firm size failed to moderate the relationship between STVA and financial performance.